Mode of action of Phialomyces macrosporus as a biocontrol agent in coffee infected with Colletotrichum sp. - Rodríguez, Gabriel Alfonso Alvarez (2016)
Colletotrichum sp. is a phytopathogenic fungus that gradually weakens both coffee seedlings and adult plants, reducing the quality of the berries. Without commercial products in the market for controlling this disease, the prospection of different biocontrol agents is a viable option. The Phialomyces macrosporus fungus stood out as a preventive control treatment for Colletotrichum in coffee seedlings, however, its mode of action has not yet been investigated. We aimed at evaluating the mode of action of P. macrosporus as a biocontrol agent in coffee seedlings infested with Colletotrichum sp. The application of P. macrosporus done seven days before the inoculation of Colletotrichum sp. reduces disease severity in 32-41%. The application of P. macrosporus on the leaves of the coffee seedlings, with and without using moist chamber, increased the permeability and rupture of the cuticle. The disturbance caused by P. macrosporus in the cuticle was followed by increased activities of PAL, CAT and POX, as well as the buildup in total phenol content and deposition of lignin. No evidence of mycoparasitism was observed either in vivo or in vitro. Due to the saprophytic nature of P. macrosporus, a decrease in the sporulation of the pathogen was observed 21 days after the application on the necrotic lesion. Nutrient competition stood out as another plausible mode of action, since both fungi presented similar niche overlap index for the use of carbon and nitrogen sources. Therefore, the saprophytic fungus Phialomyces macrosporus interfered with Colletotrichum sp. infection and survival on coffee seedlings by means of a combination of induced resistance and nutrient competition.